2020
DOI: 10.1111/jcmm.16142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed genes in oral epithelial cells infected with Fusobacterium nucleatum for revealing genes associated with oral cancer

Abstract: Periodontitis is a chronic infectious disease initiated by oral pathogenic bacterium, which not only causes local damage in oral sites, but also correlates with the pathogenesis of cancer. 1 Fusobacterium nucleatum is a commensal bacterium colonized in the human oral cavity and is considered closely associated with periodontitis. 2 In recent years, F. nucleatum has garnered a lot of attention in the initiation and progression of various malignancies, especially in colorectal cancer (CRC), through modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…For example, the placental microbiome profiles were most comparable to those of the oral microbiome [ 1 ]. The overlap of the unique members of oral microbes with other remote organs is consistent with previous clinical studies in which Fusobacterium nucleatum , a Gram-negative oral anaerobe, were clinically suspected to be a major risk factor in colorectal cancer [ 97 , 98 , 99 ], oral squamous cell carcinoma (OSCC) [ 100 ], and in preterm and term stillbirth [ 101 , 102 ]. Likewise, an infamous oral pathogenic bacterium, Porphyromonas gingivalis , is related to pancreatic cancer [ 103 ], colorectal cancer [ 104 , 105 , 106 ], liver health [ 107 ], rheumatoid arthritis [ 108 , 109 ], diabetes [ 110 , 111 , 112 ], OSCC [ 113 , 114 ], and neurodegenerative diseases [ 88 , 89 , 90 , 91 , 92 , 115 , 116 , 117 , 118 ].…”
Section: Oral Pathogens and Systemic Diseasessupporting
confidence: 86%
“…For example, the placental microbiome profiles were most comparable to those of the oral microbiome [ 1 ]. The overlap of the unique members of oral microbes with other remote organs is consistent with previous clinical studies in which Fusobacterium nucleatum , a Gram-negative oral anaerobe, were clinically suspected to be a major risk factor in colorectal cancer [ 97 , 98 , 99 ], oral squamous cell carcinoma (OSCC) [ 100 ], and in preterm and term stillbirth [ 101 , 102 ]. Likewise, an infamous oral pathogenic bacterium, Porphyromonas gingivalis , is related to pancreatic cancer [ 103 ], colorectal cancer [ 104 , 105 , 106 ], liver health [ 107 ], rheumatoid arthritis [ 108 , 109 ], diabetes [ 110 , 111 , 112 ], OSCC [ 113 , 114 ], and neurodegenerative diseases [ 88 , 89 , 90 , 91 , 92 , 115 , 116 , 117 , 118 ].…”
Section: Oral Pathogens and Systemic Diseasessupporting
confidence: 86%
“…A study using co-culture of F. nucleatum and human immortalized oral epithelial cells (HOIECs) observed the differential expression of 353 mRNAs, and the expression of multiple oncogenes, such as CREM, CREB1 and NCOA, was upregulated. An analysis of oral cancer samples in a database indicated the same trend ( Zhang et al, 2021 ). In addition, F. nucleatum bound and activated the cell inhibitory receptor CEACAM1 on CEACAM1 + TILs and CEACAM1 + tumor cells, indicating its potential importance in modulating antitumor immunity, which helped the tumor evade immune cell attack through an additive mechanism ( Gur et al, 2019 ).…”
Section: Discussionmentioning
confidence: 94%
“…Common risk factors for oral tumors include smoking, alcohol abuse, HPV, ultraviolet rays, etc. 77 , 78 In recent years, studies have found much important evidence that oral microbes are closely related to OSCC, including P. gingivalis , 79 F. nucleatum , 80 Treponema denticola 81 , 82 and Candida , 83 etc.…”
Section: Oral Bacteria and Cancersmentioning
confidence: 99%